(untitled) (Journal of Contemporary Philology, 2020)
This paper presents a multifaceted analysis of Goran Stefanovski’s play Odysseus (2012), a play which dislocates the classical Homeric myth and its established interpretations and rereads the Odyssean narration in light of the contemporary world. Stefanovski’s play appears as an inter-textual and auto-referential labyrinth, which additionally questions the frontiers between theatre/fiction and reality, replacing the Trojan War with the one in ex-Yugoslavia and recognizing today’s migrants in the character of Odysseus. Departing from the key postulates of post-colonial theory and contemporary reflections on exile and migrancy, we consider the decentering, in Stefanovski’s play, of the traditional categories of homeland, home, and identity, which here carry exile and hybridity in their heart. We also reflect on Odysseus’s impossible coming home, revealed as a second exile, but also as his last journey. Finally, we analyse the play as an example of migrant writing, while reflecting on theatre as the adopted home and dreamed Ithaca of the playwright from the diaspora, Goran Stefanovski.